Niobia-alumina supported hydroprocessing catalysts: relationship between activity and support surface acidity - Weissman, Jeffrey G. (Catalysis today, 1996)
Two classes of MoNi catalysts, surface niobium-aluminum oxides and mixed niobium-aluminum oxides, were examined for hydroprocessing of gas-oils. Niobia containing surface and mixed oxides are known to have increased surface acidities as compared to the component oxides; support surface acidity, in turn, may enhance gas-oil sulfur and nitrogen removal activities. Maximum rates of sulfur and nitrogen removal occurred for surface oxide catalysts containing 5 wt.-% Nb 2O 5, corresponding to the NbAl surface oxide support composition reported to have the highest Lewis acidity. Maximum activities, normalized on a surface area basis, occurred at a support composition of 80 wt.-% Nb 2O 3 for the mixed oxide series. Surface acidities of the Nb 2O 5A1 2O 5 supports were measured by temperature programmed reaction study of adsorbed [180]ethanol; the desorption temperature of the ether dehydration product is a relative measure of Lewis acidity. Using this method, the highest surface acidity was found on the mixed oxide supports containing 80 wt.-% Nb 2O 5. For both series of catalysts, the compositions exhibiting the greatest degree of hydrotreating activity improvement corresponded to those exhibiting the highest surface acidity. Addition of niobia to alumina readily permits surface modifications to hydroprocessing catalysts for obtaining maximum hydroprocessing activity.